Insights into corrosion behavior of AlCrFeTi and AlCrFeTiY coating for fuel cladding in static and flowing liquid lead bismuth at 550°C - Jingyi Liang; Wei Zhang; Qingyu Li; Ke Zhao; Jun Xiao; Jijun Yang; Shaoyu Qiu; Sheng Huang (Journal of Materials Research and Technology)
Corrosion resistance of AlCrFeTi and AlCrFeTiY coatings were evaluated in static and flowing lead bismuth with oxygen-controlled precondition at 550 °C, both the oxygen concentration of static and flowing liquid lead bismuth was 1 × 10−5 wt%. Double-layered compact oxide layers were formed on the surface of AlCrFeTi coating which consist of outer Fe/Cr oxide layer and inner Al/Ti oxide layer after exposure in static liquid lead bismuth for 2000 h, while uneven Fe/Cr oxide layers formed on AlCrFeTiY coating and the oxygen content significantly increase inside the coating, indicating the weaker antioxidant properties of AlCrFeTiY. Besides, structural integrity of AlCrFeTi was well preserved after erosion test in flowing lead bismuth (∼2 m/s) for 1000 h, localized bulges existed in eroded AlCrFeTiY coating. Magnetron sputtering method was utilized for coating preparation and the in-depth corrosion mechanism of AlCrFeTi and AlCrFeTiY coating was discussed.